ANALISIS KEKUATAN RANGKA, SISTEM TRANSMISI DAYA DAN KAPASITAS MESIN PENCABUT BULU AYAM ‘IDE’ 2 IN 1 PORTABEL DENGAN PENYIRAMAN 127 LANGSUNG - Irawan, Hery; Patriawan, Desmas Arifianto; Munir, Misbahul; Abdillah, Daffa`udin (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
he high demand on poultry meat has caused poultry slaughtering industries to keep innovatingto improve their productions. One of efforts to improve production is by producing a chicken featherplucker machine to ease and shorten the time to do so. Methods employed to produce this machine were:survey and literature study, chicken feather plucker machine design, machine plan calculation,component assembly, machine trial, data collection, and conclusion. This chicken feather pluckermachine was driven by electric motor ¼ HP with shaft rotary of plucker by 225 rpm. It has portabledesign with dimensions of being used by 1036 mm in length x 800 mm in width x 1300 mm in height, aswell as dimensions of being unused by 1347 mm in length x 1800 mm in width x 1300 mm in height,equipped with wheels to ease the movement to other places. The transmission system used 2 pulleys typeB and V-belt type B-25. Diameter of driving pulley was 6 inches = 152.4 mm and that of driven pulleywas 2 inches = 50.8 mm. The shaft was made of steel st60 with 25 mm in diameter and 223 mm in length.NACHI bearing 6005 with diameter of shaft hole by 25 mm was used. The results of trial reported that toprocess 2 to 4 chickens simultaneously required 3 minutes for getting the plucking result by 90%Keywords: machine, chicken feather plucker, portable